Weapons under international human rights law - Casey-Maslen, Stuart
"International human rights law offers an overarching international legal framework to help determine the legality of the use of any weapon, as well as its lawful supply. It governs acts of States and non-State actors alike. In doing so, human rights law embraces international humanitarian law regulation of the use of weapons in armed conflict and disarmament law, as well as international criminal justice standards. In situations of law enforcement (such as counterpiracy, prisons, ordinary policing, riot control, and many peace operations), human rights law is the primary legal frame of reference above domestic criminal law. This important and timely book draws on all aspects of international weapons law and proposes a new view on international law governing weapons. Also included is a specific discussion on armed drones and cyberattacks, two highly topical issues in international law and international relations"--